Genitourinary management and follow-up for patients with Stevens-Johnson syndrome/toxic epidermal necrolysis. Issue 2 (April 2023) - Baaklini, Gina T.; Mitchell, Thomas; Davis, Jordan; Cindass, Renford; McGovern, Kevin; Aden, James; Cancio, Leopold
Highlights: Genitourinary involvement in Stevens-Johnson syndrome is 68% These lesions can be treated similarly as other cutaneous lesions. Routine catheterization and urologic consultation are not necessary. Abstract: Objective: To review the cases of Stevens-Johnson syndrome and/or toxic epidermal necrolysis in adult male patients to determine the incidence of genitourinary manifestations, the indication for urethral catheters, and to provide recommendations for management. Materials and methods: This is a retrospective observational study of adult male patients over a ten year period. The study group is divided into patients with and without genitourinary manifestations. Results: We identified 57 patients who met the study inclusion criteria, of whom 39 had genitourinary involvement. The most common location of lesions was the phallus although many patients had multiple sites of involvement. These lesions were treated similarly compared to other nongenitourinary cutaneous lesions. Four patients presented with dysuria, one with frequency, and one with hesitancy and intermittency. A urethral catheter was placed in 25 of the 39 patients. None of the patients who were not catheterized and did not have lower urinary tract symptoms at the time of presentation developed voiding symptoms during their hospital stay. Apart from a one-time episode of incontinence in one patient that resolved spontaneously, none of the patients who were catheterized developed voiding issues after their catheters were removed. No patients required follow-up with urology after discharge. Conclusions: No patients developed a symptomatic urethral stricture. Many patients had multiple sites of involvement. Despite no standardized treatment being used, all cutaneous lesions were successfully treated in patients who survived their illness, with documented resolution of genitourinary lesions on physical examination. Routine urethral catheterization and urologic consultation are not necessary in these patients.